Pendidikan kristiani dan spiritualitas merawat ciptaan: Sebuah pendekatan dalam membangun sikap peduli satwa langka - Wuwung, Olivia Cherly; Polak, Nancy Eva; Iriana, Margarith (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Hunting, killing, and trafficking of wildlife are crimes against nature that are a global issue. Even though there are wildlife protection laws and regulations stipulated in international law and Law Number 5 of 1990 concerning Natural Resources Conservation, as well as the church's efforts to teach and nurture its congregation to protect and preserve God's creation, the impact is still not significant due to problems human morals. This research aims to formulate a Christian education approach to building public awareness of care for endangered animals. The method used is qualitative research with a case study approach, with the Evangelical Christian Church in Minahasa (GMIM) as one of the pioneers of collaboration with the non-governmental organization